2019
DOI: 10.3390/cancers11060883
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic Drugs Inhibiting Topoisomerase 1 Activity Impede Cytokine-Induced and NF-κB p65-Regulated Gene Expression

Abstract: Inhibitors of DNA topoisomerase I (TOP1), an enzyme relieving torsional stress of DNA by generating transient single-strand breaks, are clinically used to treat ovarian, small cell lung and cervical cancer. As torsional stress is generated during transcription by progression of RNA polymerase II through the transcribed gene, we tested the effects of camptothecin and of the approved TOP1 inhibitors Topotecan and SN-38 on TNFα-induced gene expression. RNA-seq experiments showed that inhibition of TOP1 but not of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…And the network analysis of hsa_circ_0059930 is displayed in Figure 6a and Supplementary Table 1. It has been reported that TOP1 can significantly regulate TNF and NF-κB [ 32 , 33 ]. Subsequently, TOP1 was screened through a comprehensive analysis of KEGG pathways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And the network analysis of hsa_circ_0059930 is displayed in Figure 6a and Supplementary Table 1. It has been reported that TOP1 can significantly regulate TNF and NF-κB [ 32 , 33 ]. Subsequently, TOP1 was screened through a comprehensive analysis of KEGG pathways.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that TOP1 has a significant effect in multiple biological processes, such as gene duplication, transcription, chromosome separation, and DNA repair [ 39 , 40 ]. Researches showed that topotecan, as a TOP1 inhibitor, can alleviate LPS-induced ALI by regulating NF-κB signaling pathway [ 33 ]; the activity of TOP1 can be inhibited by chemotherapeutic drugs to suppress the genes, which are regulated to cytokine and NF-κB [ 32 ]. Therefore, we speculated that TOP1 expression is in connection with ALI, which can be induced by hsa_circ_0059930.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SN38, the active metabolite of CPT-11, has been shown to increase CXCL8 secretion by enhancing the phosphorylation of MAP kinases in HCT8 cells [44]. By contrast, Riedlinger et al evidenced that topoisomerase I inhibitors interfere with cytokine-induced and NF-κB p65-mediated inflammatory gene expression in a variety of cell lines [45]. In human fibroblasts, CPT was found to increase the expression of NFKBIE and NFKBIB genes (encoding for the NF-κB inhibitors IκB-ε and IκB-β, respectively) and decrease the expression of the IKBKB gene (encoding for the NF-κB activator IKK-β) [16].…”
Section: Discussionmentioning
confidence: 99%
“…These observations are consistent with results obtained in our work, where the TOP1 expression level and the DNA replication pathway in which it is involved are positively correlated with resistance to geldanamycin analogs. Based on this, and since different TOP1 inhibitors are used clinically for the treatment of small-cell lung, ovarian, and cervical cancer [ 43 ], their use in combination with 17-AAG or IPI-504 could be an interesting therapeutic strategy to be tested in lung adenocarcinoma patients presenting with high TOP1 expression. Our results also showed that Wnt signaling could be involved in the lack of response to 17-AAG and IPI-504 due to correlations between basal abundances of SMARCC1, SMARCC2, and SMARCA5 and resistance to geldanamycin derivatives.…”
Section: Discussionmentioning
confidence: 99%